EFEKTIVITAS PENGGUNAAN APLIKASI BERBASIS GLIDEAPPS SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Mutmainna, Aisyah Sukma Nur Rahma; Julianto, Julianto (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to determine the effectiveness of using glideapps-based applications made by MI Ma'arif Sambiroto Taman Sidoarjo educators as learning media in elementary schools. This study uses a type of quantitative research with pseudo-experiments. The population used is MI Ma'arif Sambiroto Taman Sidoarjo students. Furthermore, researchers determined grade 6 as a research sample. There are two instruments in this study, namely tests and non-tests using a questionnaire to determine student responses to the results of glideapps-based applications as learning media. Hypothesis testing using t test with independent samples t test. Then the results of the student response questionnaire were at an average score of 83.8%. This shows that students' responses to the use of glideapps-based applications as learning media are very good. The results of the t test show a test value of 0.000 <0.05, so it can be seen that there is a significant difference between the two samples. It is known that the tcount value is 23.063 and the df (degree of freedom) value is 50, then the ttable is 1.676 so that it can be known that the equation is tcount (23.063) > ttable (1.676). So it is concluded that the effectiveness of glideapps-based application results between experimental and control classes is significantly different